Finger Painting as a Learning Media to Improve the Development of Painting in Early Age Childhood - Salsabila Shofika; Winnuly Winnuly; Lila Hikmawati (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Early Childhood Education (PAUD) is one place that can help the development of children. Learning requires media to develop children's development. Finger painting was chosen as a medium that can be used to enhance the development of children's art of painting at TK Dharma Wanita Pertama II Kadungrejo Bojonegoro. This study uses a qualitative method. Based on the results of the study, the researchers found that the techniques used by children to make paintings with their fingers and paint in the process of improving children's artistic development, the results of finger painting as a learning medium show that children can go through the process of forming patterns, making strokes, forming pictures and painting pictures, painting air balloons made of paper